Induction of Apoptosis by 2', 3’-Epoxyisocapnolactone and 8-Hydroxyisocapnolactone-2', 3’- Diol Isolated from Micromelum Minutum in Human T-Lymphocyte Leukemia Cem-Ss Cells - Tan, Boon Keat (2006)
2',3'-epoxyisocapnolactone and 8-hydroxyisocapnolactone-2',3'-diol are two bioactive compounds isolated from the leaves of Mzcromelum minutum. The cytotoxic effect of the compounds was tested on a variety of human cell lines respectively using MTT assay. They were found to be most sensitive against human T-lymphoblastic leukemia cells (CEM-SS). The inhibition effect of 2',3'-epoxyisocapnolactone and 8- hydroxyisocapnolactone-2',3'-diol at 50% of cell population (ICso) was found to be 4.6 pg/ml (13.5 pM) and 3 pdml (7.8 pM) on CEM-SS cells, respectively. Besides that, the inhibitor effect of the compounds on other human cells were found to be 13.4 pdml(39.2 pM) and 9.0 pdml(23.9 pM) on cervical carcinoma cells (HeLa), 14.2 pg/ml (41.5 pM) and 7.7 pdml (20.5 pM) on colon adenocarcinoma cells (HT29), 7.4 pg/ml (21.6 pM) and 5.9 pdml (1 5.7 pM) on hepatocarcinoma cells (HepG2), 6.5 pglml (19.0 pM) and 7.1 pg/ml(18.9 pM) on transform liver cells (Chang). For comparative purposes, the ICW of several clinical cytotoxic drugs against CEM-SS cells were determined. The inhibitor effect of the compounds were more significant compared with methotrexate [ICm = >30 pg/ml (66.1 pM)], cytosine arabinoside [IC5o = >30 pg/ml (123.5 pM)] and colchicines [IC50 = 8 pglml (20.1 pM)] The compounds also shown near similar ICso concentration as compare with cis-diamine dichloroplatinum [IC50 = 3 pg/ml (10.1 pM)], vinorelbine [IC50 = 3 pg/ml (3.9 pM)] and doxorubicin [IC5o = 2.4 pg/ml (4.1 pM)]. Furthermore, from proliferation assay study, the compounds were significantly inhibiting the proliferation of cells at ICso value. From the morphological observation and agarose gel electrophoresis, apoptosis of the compounds on CEM-SS cells was determined. By using phase contrast, fluorescence and electron microcopies, observation on morphological alterations indicating apoptosis was evaluated. From DNA fragmentation, Acridine orange and Propidium iodide staining and DNA content analyses, the compounds were confirmed to have ability in promoting apoptosis. However, the percentage of apoptosis induced is low and the event is time-dependent. At high concentration of 10 pg/m, 2',3'- epoxyisocapnolactone and 8-hydroxyisocapnolactone-2',3'-diol induced necrosis. Furthermore, 8-hydroxyisocapnolactone-2',3'-diol also exhibited better cytotoxicity compared to 2',3'-epoxyisocapnolactone. The induction time for apoptosis by 8- hydroxyisocapnolactone-2',3'-diol in CEM-SS is earlier than 2',3'-epoxyisocapnolactone, which is 4 hours and 12 hours after treatment. Based on the results obtained, 2',3'- epoxyisocapnolactone and 8-hydroxyisocapnolactone-2',3'-diol are able to induced apoptosis.